Mobile Voting Application for Campus Election - MUNIANDY, NUGENTHIRAN (Applied Information Technology And Computer Science, 2023)
Campus election is one of the organised procedure elections that choose a student as oneof the authorities in student council. Most of the institutes in past years performed thevoting system using paper ballot system, which will take time to get the result and havethe possibility to misplace the voting paper which lacks secure mechanisms. Apart fromthat, some universities use the electronic machine to vote for student affairs election. Soas a solution the development of online platforms now acts as a base to student votingmethodology. The online voting application is built using object-oriented analysis anddesign methodology which have requirement phase, design phase, implementation phase,verification phase and maintenance phase. The purpose to using online platforms is toreduce the workload and also to organise a stable election without any error. Apart fromthat, online elections can be secured with security features to prevent the confidentialityand integrity of the votes by applying multi-factor authentication and email verification.Mobile voting application is latest and secure technology to begin with if there are securitymechanisms like MFA token and email verification. Full release APK application file willbe tested by the (MMP) UTHM students. So, they can verify the functionality of thecampus mobile voting application.